2007
DOI: 10.1016/j.bpc.2006.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of enzyme-catalyzed reactions involving cytosine, uracil, thymine, and their nucleosides and nucleotides

Abstract: The standard Gibbs energies of formation of species in the cytidine triphosphate series, uridine triphosphate series, and thymidine triphosphate series have been calculated on the basis of the convention that Δ f G° = 0 for the neutral form of cytidine in aqueous solution at 298.15 K at zero ionic strength. This makes it possible to calculate apparent equilibrium constants for a number of reactions for which apparent equilibrium constants have not been measured or cannot be measured because they are too large.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…This equilibrium constant exists irrespective of the (bio)catalyst used and K′ values for some substrates in NPase‐catalyzed reactions have been reported . Thus, according to the law of mass action, only the reaction conditions influence the final equilibrium concentrations and not the enzyme used for catalysis.…”
Section: Introductionmentioning
confidence: 88%
“…This equilibrium constant exists irrespective of the (bio)catalyst used and K′ values for some substrates in NPase‐catalyzed reactions have been reported . Thus, according to the law of mass action, only the reaction conditions influence the final equilibrium concentrations and not the enzyme used for catalysis.…”
Section: Introductionmentioning
confidence: 88%
“…Incidentally, it has been shown that Asp185 of E. coli CMK (corresponding to Asp187 in MtCMK) plays a more relevant role in catalysis than in NMP substrate binding [13]. It has also been pointed out that whether the a-phosphate of the substrate acceptor (e.g., CMP) is protonated in phosphoryl transfer reactions remains controversial as the local enzymatic environment can influence its pK a value [43,44]. Quantum mechanics calculations have suggested that UMP/CMP kinase from Dictyostelium discoideum follows a concerted phosphoryl transfer mechanism in which the a-phosphate group of CMP is protonated [45].…”
Section: Ph Dependence Of Mtcmk:nmp Binary Complex Formationmentioning
confidence: 97%
“…Hydrolysis energies were taken from previous experiments (Alberty, 2007), but we estimate that discrepancies up to 50% may arise since the systems in the experiments were at 25°C and possibly different ionic conditions. From Table 7 of Alberty (2007), the energy of hydrolysis of CMP, UMP, and TMP is 12.96 kJ/mol, or approximately 3.1 kcal/mol per bond.…”
Section: Energy Calculationsmentioning
confidence: 99%
“…From Table 7 of Alberty (2007), the energy of hydrolysis of CMP, UMP, and TMP is 12.96 kJ/mol, or approximately 3.1 kcal/mol per bond. Two phosphoester bonds are hydrolyzed in the processing of premiRNA, and thus we take this energy of hydrolysis to be 6.2 kcal/mol.…”
Section: Energy Calculationsmentioning
confidence: 99%
See 1 more Smart Citation